PENGGUNAAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS II - Astri Fani; Wafiq Aziza Ali (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was motivated by the low learning motivation of students in mathematics subjects. This is because, in the learning process, teachers use less learning media when presenting mathematics which is known to be abstract. This research aims to increase students' learning motivation in mathematics learning by using appropriate learning media. This research is Classroom Action Research (PTK) with the research subjects being 31 class II students at UPT SD Inpres Unggulan BTN Regional Government for the 2024/2025 Academic Year. The data collection technique used in collecting data on mathematics learning motivation was a questionnaire and analyzed using descriptive statistical analysis. Based on data analysis, in cycle I, the percentage of motivation to learn mathematics for class II students using learning media reached 64% in the medium category. Cycle II, the percentage of motivation to learn mathematics increased to 74% in the high category. So these results show that the use of learning media in mathematics subjects is effective in increasing the learning motivation of class II students at UPT SD Inpres Unggulan BTN Pemda.